Consensus of Discrete-time Multi-agent Systems with White Noise Disturbance*. Issue 28 (2015) - Pan, Tingting; Mo, Lipo; Cao, Xianbing
Abstract: This paper is devoted to the consensus problem of second-order discrete-time multi- agent systems with white noise disturbance under Markovian switching topologies. Based on the information of agent and its neighbors, a control protocol is designed, which can make the systems reach bounded consensus. By means of Lyapunov function and matrix analysis method, a sufficient condition of the mean square bounded consensus is obtained. Finally, numerical simulations are given to illustrate the effectiveness of the theoretical analysis.